AN EVALUATION OF READING COMPREHENSION TEXTBOOKS TAUGHT AT THE ENGLISH EDUCATION DEPARTMENT OF ISLAMIC HIGHER EDUCATION IN WEST SUMETERA - Munir, Sirajul; Nurkamto, Joko (Language Circle: Journal of Language and Literature, 2013)
The purpose of present study is to critically assess the reading comprehension textbooks which have been prescribed for use at the English Education Department of Public Islamic Higher Education in West Sumatera. The writer used a criteria taken from CunningswothÃ¢â¬â¢ s (1995) and MiekleyÃ¢â¬â¢s (2005). These include (1) Aims and Approaches; (2) Design and Organization; (3) Content; (4) Skills; (5) Vocabulary and Grammar; (6) Exercises and Activities; (7) Methodology; (8) Attractiveness of the Text and Physical Make-Up; (9) TeacherÃ¢â¬â¢s Manual; and (10) Practical Consideration. To interpret the checklist, the four rating scale was used, namely excellent, good, fair, and poor. The research showed that every textbook has strong and weak points. The result of this analysis could be used as the basis to gain more effective reading textbooks for the lecturer of reading comprehension.